Prevalence and Sociodemographic Predictors of Depression and Anxiety among Patients with Diabetes Mellitus: A Cross-Sectional Study from an Urban Field Practice Area in Southern India - Patil, Santosh D; Rangoli, AM; Sorganvi, Vijaya; Daniel, Rachel (National Journal of Community Medicine, 2026)
Background: Diabetes mellitus is associated with significant psychological comorbidities. Limited data exist from community-based urban settings in Southern India on the prevalence and predictors of depression and anxiety among diabetic patients. The objective was to determine the prevalence of depression and anxiety among diabetes patients attending an urban field practice area and identify their sociodemographic predictors. Methods: A cross-sectional study was conducted among 100 diabetic patients (April-September 2024) at an urban field practice area, Vijayapura. Depression and anxiety were assessed using validated PHQ-9 and GAD-7 scales. Socioeconomic status was evaluated using the Modified Kuppuswamy Scale. Multivariable logistic regression identified independent predictors. Results: Depression was present in 29% (95% CI: 20.5%-38.9%) and anxiety in 31% (95% CI: 22.4%-40.9%) of participants. Muslim religion (AOR=3.1; 95% CI:1.4-9.0) and widowed/separated/divorced marital status (AOR=3.2; 95% CI:1.1-9.2) were independently associated with depression. Widowed/ separated/ divorced status (AOR=3.1; 95% CI:1.0-9.0) and illiteracy (AOR=0.2; 95% CI:0.04-0.9) were significant predictors of anxiety. Conclusion: Psychological comorbidities are highly prevalent among diabetic patients. Integrating routine mental health screening into diabetes care, particularly targeting socially and economically vulnerable individuals, is strongly recommended.